Neuropsychological case report of MCI reversion at one-year follow-up. Issue 3 (3rd May 2020) - Weissberger, Gali; Gibson, Katherine; Nguyen, Caroline; Han, Duke
Abstract: This report presents the neuropsychological profile of an older gentleman diagnosed with single-domain mild cognitive impairment (MCI) at baseline who reverted to normal cognitive functioning at 1-year follow-up. The case highlights important considerations for assessing and diagnosing MCI in clinical settings in the context of sizeable reversion rates that have been reported extensively in the literature. A 72-year-old gentleman presented to our Neuropsychology Clinic with subjective memory complaints. Per recommendation, the patient returned for follow-up testing 1-year later. A clinical interview, comprehensive battery of neuropsychological tests, and mood questionnaires were administered during both evaluations. At baseline, DSM-5 Mild Neurocognitive Disorder consistent with single-domain amnestic MCI was diagnosed based on several impaired scores on the California Verbal Learning Test, 2nd version (CVLT-II) and collateral report of subtle decline in functioning. At follow-up, all cognitive performances fell within normal limits. The patient no longer met criteria for Mild Neurocognitive Disorder. The present case study highlights important considerations when assessing and diagnosing MCI in the clinical setting. Repeat testing in clinical settings is underscored by the sizeable rate of MCI reversion reported in the literature. Important diagnostic and feedback considerations are discussed.